Assessment of the Working Posture among Dental Students to Prevent Musculoskeletal Disorders - Mohd Yusof, Eleena; Razli, Muhamad Amir Hazim; Mohd Nasir, Siti Aisyah Iman (Journal of Dentistry Indonesia, 2021)
Poor working posture among dental practitioners has been known to cause musculoskeletal disorders (MSDs), which are made worse by lengthy procedures and a lack of awareness about the proper working posture. Objectives: To assess the working posture of clinical dental students to determine if interventions were needed to reduce MSDs. Methods: The working postures of 225 clinical dental students were recorded and assessed within 10 minutes into procedures from March-December 2019, using the Rapid Upper Limb Assessment (RULA) method. The results were then statistically analysed using chi-square and Fisher’s exact tests. Results: Of the 225 students observed, 64 (28.4%; 95% CI: 23.1-35.7%) were classified as having RULA scores of 1-2 and 3-4, 141 (62.7%; 95% CI: 58.4- 65.7%) had RULA scores of 5-6 and 19 (8.4%; 95% CI:5.3-12.4%) had RULA scores of 7. Only one student had a RULA score of 1-2, where posture was considered acceptable. The working postures of the students in year 4 (P<0.001) were worse than those of the students in the other clinical years. No significant difference was observed concerning gender variance. Conclusion: Students’ working postures should be evaluated frequently, and other tools, for example, dental loupes, should be provided to help them maintain good working postures.